THERMAL OVERLOAD RELAY SEBAGAI PENGAMAN OVERLOAD PADA MINIATUR GARDU INDUK BERBASIS PROGRAMMABLE LOGIC CONTROLLER (PLC) CP1E-E40DR-A - Pradika, Hendy; Moediyono, Moediyono (Gema Teknologi, 2013)
Hendy Pradika, Moediyono, in paper thermal overload relay as a overload safety in miniature of substation based on programmable logic controller (PLC) CP1E-E40DR-AÂ  explain that at the substation there is a protective device that is very vital function, which we often refer breaker Power (PMT) or also called Circuit Breaker (CB). The function of the PMT itself is to connect or disconnect current / power corresponding branches if there is interference in substations or other transmission device or in the event of overload. At the substation's miniature PMT function is replaced by a contactor that functions more or less the same. Contactor performance is governed by OMRON CP1E PLC-E40DR-A which had previously received input from the Thermal Overload Relay in the event of overload. Thermal Overload Relay works on the principle of expansion and bimetal objects. When exposed to high current object, then the object will expand so it will bend and break the current. Excessive current will generate heat, so it can bend bimetal.Hal object will cause the contactor is connected to the Thermal Overload Relay will decide the electric current through the contactor. With this tool, we can realize the expected electric power system more secure in terms of security and reliability so as not to harm humans and the environment. Keywords: substations, protection, PMT, overload, contactors, Thermal Overload Relay, Omron PLC CP1E-E40DR-A